2016
DOI: 10.1097/j.pain.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

The α5 subunit containing GABAA receptors contribute to chronic pain

Abstract: It has been recently proposed that α5-subunit containing GABAA receptors (α5-GABAA receptors) that mediate tonic inhibition might be involved in pain. The purpose of this study was to investigate the contribution of α5-GABAA receptors in the loss of GABAergic inhibition and in formalin-, Complete Freund’s adjuvant (CFA)- and L5/L6 spinal nerve ligation-induced long-lasting hypersensitivity. Formalin or CFA injection and L5/L6 spinal nerve ligation produced long-lasting allodynia and hyperalgesia. Moreover, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 76 publications
4
48
0
Order By: Relevance
“…In contrast, some work suggests that tonic GABAergic currents can contribute to more chronic forms of pain following inflammation and nerve injury (Bravo‐Hernández et al . ). Less work has assessed the properties and roles of tonic glycinergic currents in the dorsal horn and thus the potential for different receptor stoichiometry between extrasynaptic versus synaptic GlyR pools has remained unresolved.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In contrast, some work suggests that tonic GABAergic currents can contribute to more chronic forms of pain following inflammation and nerve injury (Bravo‐Hernández et al . ). Less work has assessed the properties and roles of tonic glycinergic currents in the dorsal horn and thus the potential for different receptor stoichiometry between extrasynaptic versus synaptic GlyR pools has remained unresolved.…”
Section: Discussionmentioning
confidence: 97%
“…; Bravo‐Hernández et al . ; Perez‐Sanchez et al . ), tonic rather than synaptic inhibition is responsible for the major effect of neurosteroids on GABA A receptors (Mitchell et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been demonstrated that GABA type A receptors (GABA A Rs) are involved in the transmission of pain (5,6). GABA A Rs are ligand-gated chloride ion channel receptors (5,6).…”
Section: Introductionmentioning
confidence: 99%